2017
DOI: 10.3892/ol.2017.6359
|View full text |Cite
|
Sign up to set email alerts
|

Detection of residual metastatic tumor in the brain following Gamma Knife radiosurgery using a single or a series of magnetic resonance imaging scans: An autopsy study

Abstract: The aim of the present study was to investigate the usefulness of magnetic resonance image (MRI) for the detection of residual tumors following Gamma Knife radiosurgery (GKR) for brain metastases based on autopsy cases. The study investigated two hypotheses: i) Whether a single MRI may detect the existence of a tumor; and ii) whether a series of MRIs may detect the existence of a tumor. The study is a retrospective case series in a single institution. A total of 11 brain metastases in 6 patients were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Nonetheless, this study was limited to cross-sectional anatomical MRI data. A previous radiological-pathological correlation analysis of 11 brain metastases treated with SRS revealed that a single MRI examination could not sufficiently determine pathological failure, but that serial MRI was practical for predicting the treatment response [ 17 ]. A longitudinal study using diffusion-weighted and dynamic susceptibility contrast (DSC) perfusion-weighted imaging, which reflect tumor cellularity and vascularity, may reveal effective tools that can predict treatment resistance and local recurrence sites.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this study was limited to cross-sectional anatomical MRI data. A previous radiological-pathological correlation analysis of 11 brain metastases treated with SRS revealed that a single MRI examination could not sufficiently determine pathological failure, but that serial MRI was practical for predicting the treatment response [ 17 ]. A longitudinal study using diffusion-weighted and dynamic susceptibility contrast (DSC) perfusion-weighted imaging, which reflect tumor cellularity and vascularity, may reveal effective tools that can predict treatment resistance and local recurrence sites.…”
Section: Introductionmentioning
confidence: 99%